1999
DOI: 10.1128/jb.181.7.2044-2049.1999
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acid pH and Deficient Efflux of Pyrazinoic Acid in Unique Susceptibility of Mycobacterium tuberculosis to Pyrazinamide

Abstract: Pyrazinamide (PZA) is an important antituberculosis drug. Unlike most antibacterial agents, PZA, despite its remarkable in vivo activity, has no activity against Mycobacterium tuberculosis in vitro except at an acidic pH. M. tuberculosis is uniquely susceptible to PZA, but other mycobacteria as well as nonmycobacteria are intrinsically resistant. The role of acidic pH in PZA action and the basis for the unique PZA susceptibility of M. tuberculosisare unknown. We found that in M. tuberculosis, acidic pH enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(159 citation statements)
references
References 29 publications
1
157
1
Order By: Relevance
“…PZA is a prodrug in which the antimycobacterial activity requires hydrolysis by MTB pyrazinamidase (PZase)/nicotinamidase encoded by pncA to convert into its active form pyrazinoic acid (POA) causing cytoplasmic acidification and depletion of membrane potential. 21,48 The activity of PZA is generally thought to be dependent on acidic pH 49,50 ; however, it has recently been reported that the PZA activity can be independent of acidic pH and intrabacterial acidification. 51,52 The latter finding can be confusing as it does not mean that PZA works at neutral pH in general, irrespective of the metabolic status of the TB bacteria.…”
Section: Cross-resistance Between Inh and Eth/pth Is Discussed In Secmentioning
confidence: 99%
“…PZA is a prodrug in which the antimycobacterial activity requires hydrolysis by MTB pyrazinamidase (PZase)/nicotinamidase encoded by pncA to convert into its active form pyrazinoic acid (POA) causing cytoplasmic acidification and depletion of membrane potential. 21,48 The activity of PZA is generally thought to be dependent on acidic pH 49,50 ; however, it has recently been reported that the PZA activity can be independent of acidic pH and intrabacterial acidification. 51,52 The latter finding can be confusing as it does not mean that PZA works at neutral pH in general, irrespective of the metabolic status of the TB bacteria.…”
Section: Cross-resistance Between Inh and Eth/pth Is Discussed In Secmentioning
confidence: 99%
“…PZA is one of the most important drugs used to treat TB. PZA is a pro-drug that enters M. tuberculosis by passive diffusion and is converted to the active compound pyrazi-noic acid (POA) by a nicotinamidase/pyrazinamidase enzyme encoded by the pncA gene (Zhang et al, 1999). Hirano et al (1997) reported that 72%-97% of PZA-resistant M. tuberculosis clinical isolates carry a mutation in the coding region of the pncA gene or in its putative promoter region.…”
Section: Indirect Evidence Of Drug Transport In Mycobacteriamentioning
confidence: 99%
“…Mechanism not fully understood, though it is thought to be inhibiting vital enzyme activities and disrupting membrane transport (Heifets and Lindholm-Levy, 1992;Zhang et al, 1999;Zhang and Mitchison, 2003) Mutation in the gene pncA, preventing drug activation (Scorpio et al, 1997) Rifamycins: rifampin, rifabutin, rifalazil, rifapentine Inhibition of protein synthesis, particularly in transcriptional initiation (Kunin, 1996) and induction of programmed cell death (Engelberg-Kulka et al, 2004) Mutation in the target structural gene rpoB (Telenti et al, 1993) Riminophenazines: clofazimine, B746, B4157…”
Section: Biosynthetic Pathwaysmentioning
confidence: 99%